Keeping it local: how CD8 TRMs regulate viral and cancer immunity - Rodrigues Junior, Luiz; Bonorino, Cristina; Haubert, Alisson Felipe; Lins, Marvin Paulo; Pereira, Gabriel Pozo; Romao, Pedro R. Torres; Rouse, Barry T. (Frontiers in Immunology, 2025)
The induction of immune responses in tissues and mucosa has emerged as one of the most promising strategies for the development of more effective vaccines and immunotherapies. In this context, CD8+ resident memory T cells (CD8+ TRM) have arisen as key players in local immune surveillance, acting persistently within non-lymphoid tissues. These cells represent a new and promising frontier in local immune responses and as potential clinical tools. CD8+ TRM are being extensively investigated as therapeutic targets against viral infections and cancer, although their clinical applications have yet to be fully established. Understanding the molecular signals that regulate their generation, differentiation, maintenance, and activation is crucial for the precise targeting of their immune functions. This review explores the main mechanisms involved in the formation and maintenance of CD8+ TRM, from the strength of MHC: TCR interactions to the coordinated role of cytokines, chemokines, and transcription factors in tissue retention and the expression of markers such as CD69, CD103, and CD49a. By integrating this knowledge, we discuss strategies to manipulate these pathways with the goal of developing more effective vaccines and personalized therapies based on resident memory T cells. We also examine how these molecular signals and pathways, either independently or in combination, can be explored both in the fight against viral infections and cancer, and in identifying CD8+ TRM predictive biomarkers for response to anticancer immunotherapies across various tumor types.